From Lemongrass to Progress: Inovasi Teh Sereh sebagai Peningkatan Kesehatan dan Penggerak UMKM Di Desa Mekar Mulio, Kecamatan Sei Balai, Kabupaten Batu Bara: Pengabdian - Eisya Dalila; Putri Regina Indriani; Siti Hajar; Indira Ayu Lestari; Athiyah; Rizka Agustina Pasaribu; Dilahasana; Rahma Wulan Aprilia; Nur Azila Rahayu Putri; Aulia Nur Azmi; Ahmad Laut Hasibuan; Shinta Marito Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to explore the potential of utilizing lemongrass (Cymbopogon nardus) as a herbal tea product in Mekar Mulio Village, Sei Balai Subdistrict, Batu Bara Regency, North Sumatra. The activity was carried out through a Community Service Program (KKN) using lecture, discussion, and hands-on practice methods. The results indicated that the community, particularly PKK and Perwiritan women’s groups, showed high enthusiasm in learning the process of processing lemongrass into herbal tea. Lemongrass tea provides various health benefits, including antioxidant activity, blood pressure reduction, sleep quality improvement, and natural antimicrobial effects. Beyond its health aspects, this innovation also creates opportunities for developing Micro, Small, and Medium Enterprises (MSMEs) based on local potential. Supporting factors include the availability of raw materials, community familiarity with lemongrass, and the growing market trend for natural herbal products. Therefore, the development of lemongrass tea serves not only as a healthy beverage alternative but also as a strategic effort to empower rural communities economically.